Pre-treatment spectral CT combined with CT perfusion can predict hemorrhagic transformation after thrombolysis in patients with acute ischemic stroke. Issue 156 (November 2022) - Han, Shuting; Huang, Renjun; Yao, Feirong; Lu, Ziwei; Zhu, Jingfen; Wang, Hui; Li, Yonggang
Abstract: Objective: To investigate the value of pre-treatment spectral CT angiography (CTA) in predicting hemorrhagic transformation (HT) after intravenous thrombolysis (IVT) treatment in acute ischemic stroke (AIS) patients. Materials and Methods: AIS patients who underwent IVT with recombinant tissue plasminogen activator and pre-treatment head and neck spectral CTA and head CT perfusion (CTP) from January 2018 to June 2020 were reviewed retrospectively. Finally, 20 patients were included in the HT group and 22 age-matched patients were included in the non-HT group. Spectral and CTP parameters of the region of interest on pre-treatment CTA axial raw images and CTP images, including the infarct core (IC) and ischemic penumbral (IP) regions, were recorded. The differences in clinical variables, CTP, collateral scores and spectral parameters between the two groups were analyzed. Three multivariate logistic regression models were then developed, where model 1 included clinical and spectral parameters, model 2 included clinical and CTP parameters and a combined model included clinical, CTP, and spectral parameters. Receiver operating characteristic analysis was used to evaluate the performance of the multivariate model. Results: Patients with HT had higher Safe Implementation of Treatments in Stroke (SITS) score ( p  = 0.023), the volume of perfusion lesions ( p  = 0.005), the volume of IP ( p  = 0.003), the mean transit time (MIT) in the IC area ( p  = 0.012), as well as the TTP in IP area ( p  = 0.015) compared with patients without HT. The HT group showed significantly lower CBF in the IC area ( p  = 0.019), iodine concentration ( p  = 0.017) and the effective atomic number ( p  = 0.024) in the IP area than non-HT group. And the slope of the spectral curve of the HT group in the IP region was larger than that of the non-HT group ( p  = 0.023). Gender, age, SITS score, the volume of entire perfusion lesion, CBF and MIT in the IC area, TTP in the IP area, as well as iodine concentration in the IP area were included in the final multivariate model for predicting HT. And CBF in the IC area (OR = 0.779, 95 % CI:0.609–0.996, p  = 0.046) as well as the iodine concentration of IP area (OR = 0.343, 95 % CI: 0.131–0.901, p  = 0.030) were proved to be independent predictors for HT. The combined model including clinical, spectral, and CTP parameters, showed improved accuracy compared to the other two models, while the Delong test did not suggest a statistically significant difference (both p values > 0.05). Conclusions: The iodine concentration of IP area derived from pre-treatment spectral CTA was an independent predictor of HT after IVT treatment for AIS patients. Moreover, multivariate models combined with clinical, spectral, and CTP parameters may be able to predict HT.